2014
DOI: 10.1016/j.jcte.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic bone disease of prematurity

Abstract: Metabolic bone disease (MBD) of prematurity remains a significant problem for preterm, chronically ill neonates. The definition and recommendations for screening and treatment of MBD vary in the literature. A recent American Academy of Pediatrics Consensus Statement may help close the gap in institutional variation, but evidence based practice guidelines remain obscure due to lack of normative data and clinical trials for preterm infants. This review highlights mineral homeostasis physiology, current recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
150
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(166 citation statements)
references
References 41 publications
3
150
0
13
Order By: Relevance
“…La forma de asegurar un aporte adecuado para la mineralización ósea es la excreción urinaria de Ca y P, que debe ser > 1,2 mmol/l o > 4,8 mg/dl para el calcio y > 0,4 mmol/l o > 1,2 mg/dl para el fósforo [51][52][53] .…”
Section: Control De Evoluciónunclassified
“…La forma de asegurar un aporte adecuado para la mineralización ósea es la excreción urinaria de Ca y P, que debe ser > 1,2 mmol/l o > 4,8 mg/dl para el calcio y > 0,4 mmol/l o > 1,2 mg/dl para el fósforo [51][52][53] .…”
Section: Control De Evoluciónunclassified
“…One of the adverse outcomes of prematurity is osteopenia of prematurity and one of the risk factors for this condition is vitamin D deficiency. [3] Based on recent studies, a significant percentage of the general population suffers from vitamin D deficiency. The overall prevalence of vitamin D deficiency has been estimated at 41.6% in several studies, with the highest rate reported among black people (82.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Osteopenia, commonly known as metabolic bone disease (MBD), can be due to decreased bone mineralization or increased bone resorption [1]. Babies born prematurely (< 37th weeks of gestation or even <28th week of gestation), with very low birth weight (VLBW, <1500grams) and extremely low birth weight (ELBW, <1000grams) are at increased risk of developing the condition, called as osteopenia of prematurity [2]. This condition has drawn interest of many neonatologistsbecause of its increasing incidence over last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating inversely associated with gestational age and body weight [1,4,5,6]. Most commonly, osteopenia occurs as a result of reduced transplacental mineral delivery in preterm, poor nutritional intake and excessive mineral loss after birth [2,4]. The etiology of MBD is multifactorial which includes degree of prematurity, low birth weight, exposure to medications that can alter mineral levels, immobilization, lack of mechanical stimulation, long term parenteral nutrition, delayed establishment of full feedand inadequate nutrients intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation